Erat Autem Nox: Et Ipse Qui Exivit Erat Nox: Applying the Praeclarus Theorem to the Betrayal of Judas Iscariot. Based on John 13:26-30 - Sitepu, Edward; Waspodo, Katjuk Dhwi; Triadi, Slamet; Gooltje, Yenny (SAINT PAUL'S REVIEW, 2024)
Recognizing the figure of Judas Iscariot as a traitor provides space for polemics among theologians and congregations. Various understandings, both in positive terms (praising him as a hero) and negative (as a cursed person), leave uncertainty in interpreting the true meaning of the text. A different approach is needed but provides adequate understanding. Praeclarus' theorem is applied in his introduction to the text of John 13:26-30. This application resulted in the finding that the emphasis on Judas Iscariot's act of betrayal was the antithesis of God's plan of salvation. Satan is behind the betrayal. So it is hoped that those who want to introduce the meaning of betrayal itself is a reality that cannot be avoided, but in it Jesus gives a strong affirmation to live it by having a banquet with His disciples. This is a valuable legacy for the church when it feels betrayed.